The presence of Padaria Espiritual in the History of Press and Arts in Ceará (Patrimônio e Memória, 2012)
Padaria Espiritual (Spiritual Bakery) was one of the most unique cultural associations in Ceará and in Brasil as a whole. Many writers were involved with the association and helped to form a significant part of its artistic activities and publishing in the province of Ceará. The intention of its members was to awaken society's taste for art. As there had already been a number of artistic societies, however, many of them of a formal and rhetorical character, they decided to produce something original and even scandalous which would have an impact on the public’s taste. Antonio Sales laid out the guidelines for the organisation and was one of the major contributors to the publication of the association’s newspaper, O Pão (The Bread). Padaria Espiritual was not a society created exclusively for literature, but for arts in general, as its members consisted not only of writers and poets, but also painters, designers and musicians.
Keywords: Padaria Espiritual (Spiritual Bakery); Literary Press; Cearense Art